2013
DOI: 10.1073/pnas.1312420110
|View full text |Cite
|
Sign up to set email alerts
|

A unique secreted adenovirus E3 protein binds to the leukocyte common antigen CD45 and modulates leukocyte functions

Abstract: Significance Human adenoviruses encode Early region 3 (E3) proteins that manipulate the host immune response to establish an infection or to persist longer. To date, only a few E3 functions from a single adenovirus species (C) have been characterized, all of which act directly on infected cells. Here we describe a secreted E3 protein that is uniquely expressed by species D adenoviruses. This protein targets noninfected leukocytes using a cell surface phosphatase as a receptor. We provide evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 51 publications
4
72
0
Order By: Relevance
“…Notably, for the related adenovirus type 19a E3/49K protein, modulation of lymphocyte functions was observed only for the soluble protein and not for the membrane-resident version (51).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, for the related adenovirus type 19a E3/49K protein, modulation of lymphocyte functions was observed only for the soluble protein and not for the membrane-resident version (51).…”
Section: Discussionmentioning
confidence: 96%
“…This viral coding strategy seems to be much more common (3) than was previously anticipated. The question for a potential function of the small cleavage products of the adenovirus type 19a E3/49K protein was posed recently (51). For the small UL11 proteins, this point has to await their more careful characterization, for instance, the precise definition of the initiation codons.…”
Section: Discussionmentioning
confidence: 99%
“…Other E3 proteins protect host cells against apoptosis by down-regulating apoptosis receptors or blocking TNF-a-induced signalling (Horton et al, 1991;Shisler et al, 1997;Stewart et al, 1995). Results from a recent study revealed a unique immunomodulatory pathway that a species-specific E3 gene of HAdV-D manipulates to control the functions of noninfected leukocytes (Windheim et al, 2013). Due to its extremely large size, the E3l protein contains more transmembrane domains and immune-related motifs than the E3 proteins of HAdVs, which suggests that E3l may regulate immunomodulatory pathways and disease patterns that are distinct from those noted for the known E3 genes.…”
Section: Discussionmentioning
confidence: 99%
“…A few E3 genes are unique to a particular species and hence may allow for speciesspecific immunomodulation and differential disease outcome (3,17,18,30,31). However, with the exception of E3/49K (32), no immune evasion function for species-specific E3 proteins has been identified to date.…”
mentioning
confidence: 99%
“…E3/49K exhibits a novel processing pathway for E3 proteins. Approximately 1 h after synthesis, it is cleaved by an unknown cellular protease N-terminal to the transmembrane domain, generating a small membrane-integrated 12-14-kDa C-terminal fragment and a large ectodomain (sec49K) that is secreted or shed (32,37). sec49K is the first secreted E3 protein and the first secreted adenovirus protein known to date.…”
mentioning
confidence: 99%